New species of the genus Paravibrissina Shima (Diptera: Tachinidae) from Southeast Asia and South Pacific - Shima, Hiroshi; Tachi, Takuji (Zootaxa, 2008)
Five new species of Paravibrissina Shima are described from Southeast Asia and the South Pacific: P. argentifera sp. nov., P. aurigera sp. nov., P. leucogaster sp. nov., P. pacifica sp. nov. and P. parvula sp. nov. Paravibrissina adiscalis infuscata Shima and P. thailandica Shima are synonymized with P. adiscalis Shima (syn. nov). The female, egg and a host are known for the first time for the type species, P. adiscalis. Paravibrissina is moved to the tribe Goniini from its original placement in the Blondeliini and its systematic position is discussed in light of conflicting characters. A key to the known species of Paravibrissina is provided.